LEARNING METHODOLOGY FOR SEWING AND MODELING A STRAIGHT-CUT SKIRT BASED ON THE STEAM EDUCATION SYSTEM (Global Conference on Multidisciplinary Research and Innovation, 2026)
This paper discusses the organization of teaching methodology for sewing and modeling a straight-cut skirt based on the STEAM education system. The study highlights interdisciplinary teaching of technology, demonstrating ways to develop students’ practical sewing skills alongside logical thinking, precise calculation, engineering approaches, and aesthetic taste. Using the model of a straight-cut skirt, the processes of taking measurements, pattern making, fabric selection, cutting, sewing, and modeling are methodologically grounded in integration with STEAM components — Science, Technology, Engineering, Art, and Mathematics. This approach contributes to linking theoretical knowledge with practical activity, developing independent working skills, and enhancing technological culture among students.
Keywords: straight-cut skirt, sewing, modeling, STEAM approach, measurement taking, pattern, construction, fabric, cutting, sewing process,